2017
DOI: 10.1039/c7cp00986k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the diffusion coefficient of hydrogen ion in hydrogels

Abstract: The role of diffusion in chemical pattern formation has been widely studied due to the great diversity of patterns emerging in reaction-diffusion systems, particularly in H-autocatalytic reactions where hydrogels are applied to avoid convection. A custom-made conductometric cell is designed to measure the effective diffusion coefficient of a pair of strong electrolytes containing sodium ions or hydrogen ions with a common anion. This together with the individual diffusion coefficient for sodium ions, obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…(5). Additionally, according to the literature, the diffusion coefficients of protons in water and gel are close to D water = 8.24 × 10 -3 (mm 2 /s), obtained by scaling the water interatomic potential model 22 , and D gel = 6.22 × 10 -3 (mm 2 /s), obtained from PFGSE-NMR spectroscopy 23 , respectively. Although the measured values in the present study yield slightly lower values than the above, the diffusion coefficient of protons can be estimated using the BTB agar gel method.…”
Section: The Reaction At the Corrosion Site (Anode)supporting
confidence: 69%
“…(5). Additionally, according to the literature, the diffusion coefficients of protons in water and gel are close to D water = 8.24 × 10 -3 (mm 2 /s), obtained by scaling the water interatomic potential model 22 , and D gel = 6.22 × 10 -3 (mm 2 /s), obtained from PFGSE-NMR spectroscopy 23 , respectively. Although the measured values in the present study yield slightly lower values than the above, the diffusion coefficient of protons can be estimated using the BTB agar gel method.…”
Section: The Reaction At the Corrosion Site (Anode)supporting
confidence: 69%
“…Propagating waves of pH and bistable switches have been obtained in the gel beads, but oscillations were not observed, probably because a key requirement is the differential transport (D H . D S ) of acid and substrate, and diffusion constants for acid in gels may be lower than for dilute solutions [43]. Evidence of collective behaviour has not yet been reported in urease beads.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, Hermans, Besenius and co-workers recently reported that proton diffusion through agarose gels appeared to be faster than through other polymer gel networks, possibly as a result of its high polarity 11 – these results would support that view. There is increasing interest in the diffusion of H + through hydrogels, 26 and such issues, although of importance in reaction diffusion processes, are not yet fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Once again, this suggests that a supposedly 'inert' PG component can, nonetheless, inuence the dynamics of diffusion processes within gelswe note the importance of further studies in this important area. 26 Acid diffusion studiesoscillating gels…”
Section: Acid Diffusion Studiesexact Ph Determinationmentioning
confidence: 99%